Beurling-Type Theorem for a Class of Reproducing Kernel Hilbert Spaces - Zhi-jie Wang; Jie-sheng Xiao; Xian-min Xu (Journal of Mathematics)
In this paper, it is proved that the Beurling-type theorem holds for the shift operator on a class of reproducing analytic Hilbert spaces.